2009
DOI: 10.1111/j.1540-6520.2008.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Entrepreneurial Learning: Exploring the Link among Heuristics, Knowledge, and Action

Abstract: We extend existing theories of entrepreneurial learning and highlight the effects of heuristics under two different learning contexts: experiential learning and vicarious learning. Specifically, we argue that heuristics are consequential in explaining variations in learning. In some cases, heuristics can be highly adaptive and beneficial to the accumulation of knowledge. In others, they can distort judgments and bias learning. By considering linkages among heuristics, knowledge, and action, we seek to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
307
5
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 309 publications
(335 citation statements)
references
References 150 publications
(234 reference statements)
3
307
5
20
Order By: Relevance
“…As an effect, it is found that entrepreneurial learning could improve business outcome (Shyh-Rong Fang et al 2014;Wang 2008). However, the characteristic of learning is rough and intense in entrepreneurial ventures; where entrepreneurs often rely on their limited knowledge and make decisions without conducting exhaustive analysis (Holcomb, Ireland, Holmes & Hitt 2009;Stokes & Blackburn 2002). That being said, entrepreneurial success depends on high intensity of learning, which has long been implied by Frese's concept of entrepreneur-in-action (2009).…”
Section: Market Orientation and Entrepreneurial Learning Intensitymentioning
confidence: 99%
See 4 more Smart Citations
“…As an effect, it is found that entrepreneurial learning could improve business outcome (Shyh-Rong Fang et al 2014;Wang 2008). However, the characteristic of learning is rough and intense in entrepreneurial ventures; where entrepreneurs often rely on their limited knowledge and make decisions without conducting exhaustive analysis (Holcomb, Ireland, Holmes & Hitt 2009;Stokes & Blackburn 2002). That being said, entrepreneurial success depends on high intensity of learning, which has long been implied by Frese's concept of entrepreneur-in-action (2009).…”
Section: Market Orientation and Entrepreneurial Learning Intensitymentioning
confidence: 99%
“…Although MO and learning are synergistic in understanding business performance in marketing literature, entrepreneurship literature emphasizes more on intense and continuous learning in attaining entrepreneurial success (Cope 2003;Rae & Carswell 2001;Holcomb et al 2009). According to Cope (2003) entrepreneurs learn much from discontinuous experiences where they invest significantly in terms of mental and emotional commitment to learn new knowledge.…”
Section: Mediation Hypothesismentioning
confidence: 99%
See 3 more Smart Citations